'It is never good. Really, it's just never good': a dominant theme in the life story accounts of strictly Reformed-raised emerging adults about their religious identity development. Issue 2 (3rd April 2022) - de Bruin-Wassinkmaat, Anne-Marije; de Kock, Jos; Visser-Vogel, Elsbeth; Bakker, Cok; Barnard, Marcel
ABSTRACT: This article presents a striking finding of our research into the religious identity commitments and process of religious identity development of emerging adults who grew up in strictly Reformed contexts in the Netherlands. We observed a recurrent theme in the life story accounts we studied. Almost all the participants expressed that they feel or felt not good enough for God or believers within strictly Reformed contexts. In this article, we explore this theme and show how feelings of not being good enough are related to various aspects of participants' strictly Reformed upbringing, such as specific beliefs and specific ideal images. In addition, we show which experiences go along with feelings of not being good enough. Last, we discuss the findings, provide suggestions for future research and point to directions for further reflections by educators.